Pengaruh hide poison dan formalin terhadap sifat kulit dalam pengawet kulit kambing secara dikeringkan - Sunaryo, Ignatius; Widari, Widari; Suryaningsih, Puji Ediari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1991)
The objective of this study is know the effect of ide poison and formaline in the dried curing of goat skin. This study used 199 goat skins that were devided into seven groups od curing. Each group consisted of 17 goat skins. Those groups were : 3 groups of dried curing by hide poison of 0,1%, 0,3% and 0,5%; 3 groups of dried curing by formaline of 1%, 3% and 5%; and 1 groups of dried curing without any preserevation agent as control. After having stored for about 4 months, those skins then to be analized. Physical and chemical analysis werw carried out to evaluate the quality of the skin. Completely randomized design by Duncanâs test was used to analyze the dta. Based on this statistical analysis we can know that: the effect of hide poson in the dried curing of goat skins was the best. The quality of goat skins that were cured by hide poison was as follows : - the average tensile strength was the highest (886,30 kg/CM2), - the average of stretch was the lowest (14,50%), - the average iof hardness was the highest (201,90 kg/2,54 Cm), - the water content was the lowest (20%), and the damage was the smallest (10%).